Unblurring the lines: a qualitative exploration of young women’s opinions on popular music - McCallum, J.; Dzidic, Peta (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Music is an important part of the human experience, arguably contributing to identity and the formation of relationships and group memberships. However, the way women are portrayed in music has been identified as harmful and disempowering. Past research relating music to these trends has often failed to “give voice” to participants by asking them what think about the music they listen to, which is in itself disempowering. Therefore, the aim of this study was to gain an understanding of young women’s perspectives of popular music. Face-to-face, in-depth, semi-structured interviews were conducted with 10 young women. Causal layered analysis was used to deconstruct participants’ understandings of popular music. Findings revealed that for participants, music can both reflect and contribute to conflicting worldviews regarding women’s freedom of expression and sexual conservatism. Music also acted as a conduit for discussion of the social construction of women; participants articulated that female artists are seen rather than heard, reduced to body parts and commodified. Findings indicate that participants are cognizant of gendered power differences in music, rendering popular music in particular a mechanism for the oppression of women, but also a useful means to monitor and challenge problematic cultural attitudes directed at women.